Konsep Kepemimpinan Pendidikan Islam dalam Memajukan Pendidikan Anak Usia Dini - dea pradita widyanto , Arifuddin jalil (Hamka Ilmu Pendidikan Islam, 2025)
ABSTRACT This study aims to examine the concept of leadership in Islamic education and its relevance to advancing early childhood education (ECE). Using a descriptive-analytical approach and a library research method, this article explores core values in Islamic leadership such as trustworthiness (amanah), exemplary conduct, consultation (shura), and spiritual responsibility. These values are analyzed within the context of early childhood education practices that emphasize character formation and moral development from an early age. The findings indicate that the application of Islamic educational leadership concepts can foster the creation of a religious, enjoyable, and holistic learning environment. Leaders of ECE institutions who implement Islamic leadership principles have the potential to enhance teacher quality, strengthen collaboration between teachers and parents, and cultivate Islamic character in children. Thus, Islamic leadership plays an essential role in integrating religious values into the process of early childhood education in a sustainable manner. Keywords: Islamic Leadership, Islamic Education, Early Childhood, ECE, Spiritual Values